"Huwag magpakatuta!" journalism ethics in the Philippines - Duran-Apostol, Eugenia (2005)
The UP Gawad Plaridel is the sole award given to outstanding media practitioners in the University of the Philippines (UP) system. The award is named after Marcelo H. del Pilar (nom de plume, Plaridel), the selfless propagandist whose stewardship of the reformist paper La Solidaridad helped crystallize nationalist sentiments and ignite libertarian ideas in the 1890s. Like Plaridel, the recipient of the award must believe in the vision of a Philippine society that is egalitarian, participative, and progressive, and in media that are socially responsible, critical, and vigilant. For the year 2004, the award was given to a print media practitioner ? Eugenia Duran-Apostol. She was cited, among others, for the ?body of her publications and works which have been consistently marked by excellence, integrity, and social responsibility, qualities which the UP College of Mass Communication wishes to develop among students and professionals in the field of media?. As the 2004 awardee, Apostol delivered this Plaridel Lecture 2004 titled ?Huwag Magpakatuta! (Journalism Ethics in the Philippines)? on November 22, 2004 at the UP Film Institute Cine Adarna (formerly UP Film Center). About 750 people attended the event, among them National Artists F. Sionil Jose, Napoleon Abueva, and Virgilio Almario; then UP President Francisco Nemenzo and former UP President Jose Abueva; Philippine Daily Inquirer (PDI) Editor-in-Chief Letty Jimenez-Magsanoc and other section editors; PDI Publisher Isagani Yambot and other staff members; Philippine Center for Investigative Journalism Executive Director Sheila Coronel; Foundation for Worldwide People Power President Maria Lim-Ayuyao; faculty members and mass communication students from UP and other universities. Officials and faculty members from the Ateneo de Manila University, Centro Escolar University, De La Salle University (Dasmariñas), Far Eastern University, Kalayaan College, Manila Doctors College, Miriam College, Polytechnic University of the Philippines, University of the East, and University of Santo Tomas were also present.
Includes bibliographical references.